REPRESENTATION OF RACIAL DISCRIMINATION AGAINST THE MAIN CHARACTERS IN THE FILM EVERYTHING EVERYWHERE ALL AT ONCE (2022) - Rizkia, Adella (﻿Kantor Bahasa Provinsi Bangka Belitung, 2023)
This research study racial discrimination against the Asian characters in the film Everything Everywhere All at Once (2022). The aim of this research is to analyze racial discrimination against the Asian characters in the film Everything Everywhere All at Once (2022). The theory used in this research is Orientalism by Edward W. Said. This theory used to analyze racial discrimination against the Asian characters. This research used qualitative descriptive methods to produce descriptive data in the form of written and verbal data from the objects studied. The results of this research show that there are (7) data showed racial discrimination against the Asian characters. There are (3) data that found on protagonist character, there are (1) data that found on antagonist character, and there are (3) data on tritagonist character.